Appraisal and evaluation in Zimbabwean parliamentary discourse and its representation in newspaper articles - Jakaza, Ernest (Stellenbosch University, 2016)
Dissertation presented for the degree of Doctor in Philosophy in the Faculty of Arts and Social Sciences at Stellenbosch University